Vegetation Characteristics and their Effect on Runoff and Peak Rates from Small Watersheds - Mathur, H. N.; Sajwan, S. S. (Indian Forester, 1978)
Two small brush wood watersheds W1F (1.45 ha) and W2F (.87 ha) were calibrated between 1961-68 and W1F was clearfelled and planted up with two species of Eucalyptus in 1969. Analyis of precalibration data 1961-68 indicated that W2F gave 18% less runoff & 63% lower peak rates as compared to W1F. Data analysis for the post treatment period 1969-74 indicated that W1F now gives 28% less runoff and 73% lower peak rates as compared to W2F. In order to find out the causes for this reduction, the vegetation in the two watersheds was surveyed and it was found out that W1F has 21 % more ground cover, 24% more trees, 39% more leaf litter, 68% more above ground and 11 % more under ground phytomass.